Kredit, banki i denežnoe obraščenie ([s.n.], 1873)
Collection Marx-Engels Library. Various written annotations by Karl Marx on pages 107-340; contains on pages 107 and 327 notelets with Marx' notes deciphered probably by B.I. Nikolaevskij.